How to Define Mild to Severe Hidradenitis Suppurativa? A Simple New Tool Based on Latent Class Analysis of EPIVER Data Study - Perrot JL; Maccari F; Guillem P; Fougerousse AC; Nassif A; Beneton N; Cinotti E; Girard C; Binois R; Reguiaï Z (Dove Medical Press, 2022)
Jean-Luc Perrot,1,2 François Maccari,2,3 Philippe Guillem,2,4– 6 Anne-Claire Fougerousse,2,7 Aude Nassif,2,8 Nathalie Beneton,2,9 Elisa Cinotti,2,10 Céline Girard,2,11 Raphaelle Binois,2,12 Ziad Reguiaï2,13 On behalf of the ResoVerneuil group1Department of Dermatology, University Hospital of Saint-Etienne, Saint-Etienne, France; 2ResoVerneuil, Ville, France; 3Private Office, La Varenne St Hilaire, France; 4Service de chirurgie adulte, clinique du Val-d’Ouest, Ecully, 69130, France; 5European Hidradenitis Suppurativa Foundation, Dessau, Germany; 6Groupe de Recherche En proctologie de la Société Nationale Francophone de Colo-Proctologie, Paris, France; 7Military Teaching Hospital Bégin, Saint Mandé, France; 8Centre Médical de l’Institut Pasteur, Paris, 75015, France; 9Dermatology Department, Centre Hospitalier du Mans, Le Mans, France; 10Department of Medical, Dermatology Unit, Surgical and Neuro.Sciences, University of Siena, Siena, Italy; 11Dermatology Department, Centre Hospitalier Universitaire de Montpellier, Montpellier, France; 12Dermatology Department, Centre Hospitalier Régional d’Orléans, Orléans Cedex, 45067, France; 13Service de dermatologie, polyclinique Courlancy, Reims, 51100, FranceCorrespondence: Jean-Luc Perrot, Department of Dermatology, University Hospital of Saint-Etienne, Saint-Etienne, France, Email j.luc.perrot@chu-st-etienne.frPurpose: Hidradenitis suppurativa (HS) is an inflammatory skin disease characterized by recurrent or chronic painful and suppurating lesions in the apocrine gland-bearing regions. The lack of knowledge about HS and its extremely heterogeneous clinical presentation, in terms of both lesion appearance and sites of involvement, frequently delay its diagnosis for several years. Objectives: in this study, using the latent class analysis, it was demonstrated that severity of HS could be evaluated not only with clinical or surgical characteristics but also with gender specificities.Patients and Methods: Clinical and sociodemographic data of HS patients were retrospectively analysed with the latent class method in order to create a classification tool of disease severity.Results: From the study of 1428 HS patients (544 men and 884 women), two classification models, depending on gender, were developed. Each classification model was composed of three distinct latent classes clearly identified and defined from mild-to-severe cases of HS. These classification models of HS severity were not distorted by patient ages and were coherent with Hurley stages but were more clinically precise.Conclusion: In this study, a convenient classification tool, useful for facilitating decision support in routine practice, has been developed. This tool could be used to define clinical subgroups within a study population.Keywords: hidradenitis suppurativa, classification, severity, latent class, Hurley stage